Perfil hematológico e bioquímico de cães (Canis familiaris) obesos e idosos - Martins, Christina Resende (2012)
Obesity is considered the most common nutritional disorder in developed societies, being defined as a pathological disorder characterized by accumulation of fat at levels higher than necessary for optimal organ function. Influenced by several factors, the life expectancy of dogs has increased, making this population increasingly composed of elderly individuals. With advancing age, irreversible physiological changes occur resulting in organ dysfunction, and many systems are affected by these changes. Therefore, knowledge of the main hematological and serum biochemistry that obese dogs suffer as they age, is of great help to the clinician of small animals, potentially enabling a better approach to this patient. In this context, the objective was to evaluate the hematological and biochemical profile of dogs, and elderly adults suffering from obesity by natural causes. In chapter 2 we evaluated the blood counts of 30 adult dogs and 29 elderly dogs, found regardless of age and sex, dogs showed no significant changes in platelet and red blood cell, showing only a slight increase in leukocyte counts of young cells without leukocytosis. In chapter 3, we avaluated the serum biochemical profile in these animals, and regardless of age and sex, obesity and old age didn t affect the values of alkaline phosphatase, alanine aminotransferase, total protein, albumin, creatinine, glucose, total cholesterol and triglycerides. Globulins were slightly higher in both groups. Serum GGT was much higher than values adopted in old females. Also observed that for both groups, the LDL-C were the highest concentration of serum lipoproteins, followed by HDL-C and VLDL-C.